2015
DOI: 10.1166/jnn.2015.9533
|View full text |Cite
|
Sign up to set email alerts
|

A Point-of-Care Prothrombin Time Test on a Microfluidic Disk Analyzer Using Alternate Spinning

Abstract: In this study, we conducted a fully integrated point-of-care prothrombin time test on a microfluidic disk analyzer. The microfluidic functions integrated on the disk were capable of separating whole blood, decanting plasma, and mixing it with reagents in sequence under alternate spinning. The assay protocol was completed by alternate spinning without using microvalves or surface modification. Clinical sample tests on prothrombin time measurement were conducted by both the microfluidic disk analyzer and the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Compared with other microfluidic chips, disc microfluidic chips have the ability to centrifuge and separate whole blood samples due to their structural advantages. On this basis, disc microfluidic technology can directly carry detection methods consistent with laboratory tests, which is more conducive to building a diagnostic system for consistency between clinical and laboratory coagulation function test results (Lin CH, et al, 2015).…”
Section: Dynamic Current Methodmentioning
confidence: 99%
“…Compared with other microfluidic chips, disc microfluidic chips have the ability to centrifuge and separate whole blood samples due to their structural advantages. On this basis, disc microfluidic technology can directly carry detection methods consistent with laboratory tests, which is more conducive to building a diagnostic system for consistency between clinical and laboratory coagulation function test results (Lin CH, et al, 2015).…”
Section: Dynamic Current Methodmentioning
confidence: 99%
“…This system reduced the processing time and reagent consumption by an order of magnitude. Lin et al [20] demonstrated a POC device in which decanting and mixing were performed by alternating the spin direction, and the process was completed within 2 s.…”
Section: Fabrication Of Sample Cartridgementioning
confidence: 99%
“…The motor control system, which is capable of conducting precise spinning control and is used to evaluate the performance of the fluidic function, was mentioned in our previous work. 7,24 To observe the fluid flow under rotation, a high-speed complementary metal oxide semiconductor camera (AVT BONITO CL-400C, Allied Vision, USA) and a stroboscope (DT-311N, SHIMPO, Japan) were used to capture images of the disk at the same location. The images were analyzed using computer software (Vision Assistant 2015, Nation Instrument, USA) to acquire information required for liquid volume quantification and flow field analysis.…”
Section: Disk Fabrication and Flow Visualizationmentioning
confidence: 99%